WHAT MARKETING CAPABILITIES MATTER IN SERVICE DIGITALIZATION? A STRUCTURED ABSTRACT REVIEW - Melisa Maria Gosal; Daniel Peterson Silaban (Dynamic Management Journal, 2026)
Digital transformation is reshaping service industries and increasing the importance of marketing capabilities for maintaining competitiveness in digitally mediated environments. This study presents a structured systematic literature review of research on digital service marketing capabilities using an abstract-based analysis of 22 Scopus-indexed studies published between 2021 and 2026. The review identifies five dominant capability types: communication capability, customer interaction capability, platform ecosystem capability, analytics capability, and service experience capability. The findings indicate that communication capability remains the most frequently discussed, while analytics and platform capabilities represent emerging directions. Sectoral analysis shows variations across industries, with platform sectors emphasizing ecosystem participation, tourism focusing on customer experience, and banking highlighting analytics and relationship management. The review also suggests that digital marketing capabilities tend to develop progressively through capability building, integration, and strategic transformation rather than simple technology adoption. These findings contribute to understanding digital service marketing capability development and provide implications for future research.Digital transformation is reshaping service industries and increasing the importance of marketing capabilities for maintaining competitiveness in digitally mediated environments. This study presents a structured systematic literature review of research on digital service marketing capabilities using an abstract-based analysis of 22 Scopus-indexed studies published between 2021 and 2026. The review identifies five dominant capability types: communication capability, customer interaction capability, platform ecosystem capability, analytics capability, and service experience capability. The findings indicate that communication capability remains the most frequently discussed, while analytics and platform capabilities represent emerging directions. Sectoral analysis shows variations across industries, with platform sectors emphasizing ecosystem participation, tourism focusing on customer experience, and banking highlighting analytics and relationship management. The review also suggests that digital marketing capabilities tend to develop progressively through capability building, integration, and strategic transformation rather than simple technology adoption. These findings contribute to understanding digital service marketing capability development and provide implications for future research.